2017
DOI: 10.1007/s00281-017-0639-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine storm and sepsis disease pathogenesis

Abstract: Infectious diseases are a leading cause of death worldwide. Sepsis is a severe clinical syndrome related to the host response to infection. The severity of infections is due to an activation cascade that will lead to an autoamplifying cytokine production: the cytokine storm. Cytokines are a broad category of relatively small proteins (<40 kDa) that are produced and released with the aim of cell signaling. Our understanding of the processes that trigger this tremendous amount of cytokine production has made dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
854
0
35

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,045 publications
(902 citation statements)
references
References 123 publications
13
854
0
35
Order By: Relevance
“…#p < 0.05, when compared with untreated sepsis group; ##p < 0.01, when compared with untreated sepsis group Systematic inflammation response is considered a hallmark of sepsis. Among the numerous proand anti-inflammatory cytokines studied during sepsis, TNF-α and IL-10 are of crucial importance [19]. In this study, it was demonstrated that EGCG treatment relieved the inflammation during sepsis.…”
Section: Discussionmentioning
confidence: 61%
“…#p < 0.05, when compared with untreated sepsis group; ##p < 0.01, when compared with untreated sepsis group Systematic inflammation response is considered a hallmark of sepsis. Among the numerous proand anti-inflammatory cytokines studied during sepsis, TNF-α and IL-10 are of crucial importance [19]. In this study, it was demonstrated that EGCG treatment relieved the inflammation during sepsis.…”
Section: Discussionmentioning
confidence: 61%
“…Chromosomal DNA was detected in the supernatants after infection with WT bacteria 4 h post-injection, whereas negligible or no chromosomal DNA was detected in the supernatant after infection with Δpep27 , suggesting that this mutant is not capable to induce lysis and hence no chromosomal DNA could be detected in supernatant (Figure 3(g)), indicating that the Δpep27 cells were rapidly cleared. Since the proinflammatory cytokines produced within 6 h post-infection play a critical role in septic shock [1821], the lysis-resistance of bacterial cells was corroborated by measuring the proinflammatory cytokines 6 h after i.n . infection.…”
Section: Resultsmentioning
confidence: 99%
“…They can cause the activation, proliferation, and/or motility of target cells [2]. Signaling is achieved by time-and space-compartmentalized processes and amplification cascades wherein the controlled release of certain DOI: 10.1159/000492379 cytokines, in turn, stimulates the local or remote release of others [3]. Imbalances of pro-and anti-inflammatory cytokines lie at the center of systemic inflammatory responses and multi-organ dysfunction syndrome (MODS) [4,5].…”
Section: Cytokines and The Immune Systemmentioning
confidence: 99%